IMPLEMENTASI METODE SIMPLE ADDITIVE WEIGHTING PADA PEMILIHAN DESA PENERIMA KEGIATAN TMMD KOREM 042/GAPU : FMADM;Korem 042/GAPU;Simple Additive Weighting;Decision Support System;TMMD. - Wahyuning Astuti, Reny; Rifkianda, M. Anugrah (JURNAL AKADEMIKA, 2022)
Village selection for the Manunggal Army Building a Village (TMMD) activity at Korem 042/GAPU is still using the manual method, making it difficult to select and consider villages that are entitled to receive assistance. The method used is Fuzzy Attribute Decision Making (FMADM) to determine the results of the selection of each alternative and the calculation in this study uses Simple Additive Weighting (SAW), then calculations are carried out on each predetermined criterion. The results of this research are web-based. The data input into this system is in the form of population, village name, village address, data on the criteria for the most prioritized infrastructure facilities, data on budget funds criteria, and data on criteria for mileage from the village to the city. Then carry out the data input process and produce output in the form of recommendations for which villages are entitled to receive assistance from TMMD activities. By using this system, it is hoped that the activity organizers can determine which villages are entitled to receive assistance appropriately and efficiently.